1997
DOI: 10.4315/0362-028x-60.5.485
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Steam Pasteurization Process in a Commercial Beef Processing Facility

Abstract: The effectiveness of a steam pasteurization process for reducing naturally occurring bacterial populations on freshly slaughtered beef sides was evaluated in a large commercial facility. Over a period of 10 days, 140 randomly chosen beef sides were microbiologically analyzed. Each side was sampled immediately before, immediately after, and 24 h after steam pasteurization treatment. Total aerobic bacteria (APC), Escherichia coli (generic), coliform, and Enterobacteriaceae populations were enumerated. The proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(33 citation statements)
references
References 0 publications
0
30
2
1
Order By: Relevance
“…For example, Table 1 Estimates of R, B and A and of goodness of fit (% variance) for the negative exponential equation and standard deviation between replicates (SD R ) and between times (SD T ) after treatment for 6.0-8.0 s, the data of Nutsch et al (1997Nutsch et al ( , 1998 at steam/air temperatures of 92 and 82°C, show reductions of about 1.0-1.5 logs for TVCs. These reductions are in contrast to those of Minihan et al (2003) of only about 0.5 of a log or less after heating at 90°C for 10 s. This shows that the reductions obtained in different studies cannot be compared, because the recorded temperatures refer to different locations, either on the carcass surface or in the chamber i.e.…”
Section: Discussionmentioning
confidence: 98%
“…For example, Table 1 Estimates of R, B and A and of goodness of fit (% variance) for the negative exponential equation and standard deviation between replicates (SD R ) and between times (SD T ) after treatment for 6.0-8.0 s, the data of Nutsch et al (1997Nutsch et al ( , 1998 at steam/air temperatures of 92 and 82°C, show reductions of about 1.0-1.5 logs for TVCs. These reductions are in contrast to those of Minihan et al (2003) of only about 0.5 of a log or less after heating at 90°C for 10 s. This shows that the reductions obtained in different studies cannot be compared, because the recorded temperatures refer to different locations, either on the carcass surface or in the chamber i.e.…”
Section: Discussionmentioning
confidence: 98%
“…low temperature, relative humidity, air speed and water activity (Nottingham, 1982) and even can cause stress and kill certain proportion of bacterial cells. The actual evidence as to whether such effects result in Salmonella reductions that are of significant practical relevance is limited and conflicting (Gill & Bryant, 1997;McEvoy et al, 2000;Nutsch et al, 1997). Results from some more recent studies suggested that as great as 4-log reduction of artificially inoculated Salmonella on beef can be achieved by slow-aging (21 days) dry chilling regime (Tittor et al, 2005) which is usually accompanied by higher weight loss and used only by small operators.…”
Section: Beef Carcass Chillingmentioning
confidence: 93%
“…HACCP systems should be based on microbiological data that allow for estimation of the numbers of indicator organisms on meat products at various processing stages (Gill, 2000). The current approach to assessing microbial contamination of meat carcass at slaughterhouses and meat processing plants is to collect samples by excising or swabbing (Nutsch et al ., 1997). For raw meat products, safety and quality can be estimated using indicator microorganisms, and by subsequently obtaining the total aerobic plate count (APC), coliform count (CC), and E. coli (ECC) count (Jay, 1992).…”
Section: Introductionmentioning
confidence: 99%